Urgensi Pendaftaran Warisan Budaya Indonesia Secara Internasional dan 2 Usulan Strategi Kebijakan - Taufik H. Simatupang; Asmak Ul Hosnah; Djamilus Djamilus; Ahmad Sanusi (Jurnal Ilmiah Kebijakan Hukum, 2024)
Indonesia already has many cultural heritages that are registered nationally, but only a few have been registered and received world recognition. This research aims to determine the level of cultural heritage registration that has been carried out and provide suggestions and recommendations for accelerating the registration in question. This study uses a normative legal research method using secondary data through literature studies. Data is obtained from national and international websites, data is analyzed and interpreted using relevant legal theories, conclusions are based on deductive thinking logic. The results of the research show that cultural heritage registrations that have been carried out from 1991 - 2023 are 10 registrations, each year only 0.31 registrations are recorded, meaning less than 1 registration per year. For intangible cultural heritage registrations that have been carried out from 2008 - 2023, there are 13 registrations, each year only 0.87 registrations are recorded, meaning less than 1 registration per year. This registration level is very small when compared with the number of communal intellectual properties recorded until 2024, namely 10,533 communal intellectual properties. To gain world recognition for Indonesia's cultural heritage, a more progressive legal policy strategy is needed, namely sui generis legal strengthening in the field of communal intellectual property and a management policy strategy for more massive involvement, from all regional and central stakeholders, to be equally involved actively and encourage of registration of Indonesian cultural heritage in international institutions.